MAIZE HYBRIDS PRODUCTION FOR DIRECT CONSUMPTION BY THREE –WAY CROSSES - Kazem, Kamal; Abed, Nadhum (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
ABSTRACT This study was aimed to produce and evaluate 30 triple cross hybrids generated by crossing ten single hybrids with five genetically diverse inbred lines. A field experiment was conducted using five inbred lines of maize: (1) NADH 102, (2) NASA 2022, (3) NAEL 2022, (4) NA 9928 E, and (5) NADH 2006. In the first spring season 2022, the genetic materials used by half-diallel crosses program to produce (10) single crosses. In the fall season, parental inbred lines and single crosses were subjected to a triple hybridization program. The results of this study revealed significant differences among the genotypes, of triple hybrid (2×5) ×3 produced the highest yield per unit area for both seasons at 23.41 and 23.55 tons ha-1. But did not significantly differ from the triple hybrids (1×3) ×2, (2×3) ×4, and (2×4) ×1, which yielded 22.19, 22.82, and 20.88 tons ha-1, respectively. The superiority of the triple hybrid (2×5) ×3 could be attributed to its higher, increased number of kernel row per ear, resulting in a higher weight of ears, which reached 556.5 and 553.4 gm for both seasons, as well as the highest yield per individual plant, reaching 439.2 and 441.5 grams.